Protonation of a Peroxodiiron(III) Complex and Conversion to a Diiron(III/IV) Intermediate: Implications for Proton-assisted O-O Bond Cleavage in Nonheme Diiron Enzymes - Cranswick, Matthew A. (2012)
Oxygenation of a diiron(II) complex,[Fe(II)(2)(μ-OH)(2)(BnBQA)(2)(NCMe)(2)](2+ )(2) (where BnBQA is N-benzyl-N,N-bis(2-quinolinylmethyl)amine) results in the formation of a metastable peroxodiferric intermediate (3). Treatment of 3 with strong acid affords its conjugate acid 4 in which the (μ-oxo)(μ-1,2-peroxo)diiron(III) core of 3 is protonated at the oxo bridge. The core structures of 3 and 4 are characterized in detail by UV-vis, Mössbauer, resonance Raman, and X-ray absorption spectroscopies. Complex 4 is shorter lived than 3 and decays to generate in 20–25% yield a diiron(III/IV) species (5) that can be identified by EPR and Mössbauer spectroscopy. This reaction sequence demonstrates for the first time that protonation of the oxo bridge of a (μ-oxo)(μ-1,2-peroxo)diiron(III) complex leads to the cleavage of the peroxo O–O bond and formation of a high-valent diiron complex, thereby mimicking the steps involved in the formation of intermediate X in the activation cycle of ribonucleotide reductase.